Reduced leu operon expression in a miaA mutant of Salmonella typhimurium. - Blum, P H (1988)
Salmonella typhimurium miaA mutants lacking the tRNA base modification cis-2-methylthioribosylzeatin (ms2io6A) were examined and found to be sensitive to a variety of chemical oxidants and unable to grow aerobically at 42 degrees C in a defined medium. Leucine supplementation suppressed both of these phenotypes, suggesting that leucine synthesis was defective. Intracellular levels of leucine decreased 40-fold in mutant strains after a shift from 30 to 42 degrees C during growth, and expression of a leu-lacZ transcriptional fusion ceased. Steady-state levels of leu mRNA were also significantly reduced during growth at elevated temperatures. Failure of miaA mutant leu-lacZ expression to be fully derepressed during L-leucine limitation at 30 degrees C and suppression of the miaA mutation by a mutation in the S. typhimurium leu attenuator suggests that translational control of the transcription termination mechanism regulating leu expression is defective. Since the S. typhimurium miaA mutation was also suppressed by the Escherichia coli leu operon in trans, phenotypic differences between E. coli and S. typhimurium miaA mutants may result from a difference between their respective leu operons.